2022
DOI: 10.3389/fcell.2022.827940
|View full text |Cite|
|
Sign up to set email alerts
|

Calcium Homeostasis in the Epididymal Microenvironment: Is Extracellular Calcium a Cofactor for Matrix Gla Protein-Dependent Scavenging Regulated by Vitamins

Abstract: In the male reproductive tract, the epididymis is an essential organ for sperm maturation, in which sperm cells acquire mobility and the ability to fertilize oocytes while being stored in a protective microenvironment. Epididymal function involves a specialized luminal microenvironment established by the epithelial cells of epididymal mucosa. Low-calcium concentration is a unique feature of this epididymal luminal microenvironment, its relevance and regulation are, however, incompletely understood. In the rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 232 publications
0
9
0
3
Order By: Relevance
“…Sertoli cells extend from the basilar membrane to the area around germ cells and form a supporting system. During the entire spermatogenesis process in mammals, Sertoli cells provide physical support via intercellular interactions, and provide nutrients by secreting lactate, cytokines, and androgen (6,12). Sertoli cells promote the development from germ cells to sperm via intercellular connections and regulation of the seminiferous tubule environment (9).…”
Section: Discussionmentioning
confidence: 99%
“…Sertoli cells extend from the basilar membrane to the area around germ cells and form a supporting system. During the entire spermatogenesis process in mammals, Sertoli cells provide physical support via intercellular interactions, and provide nutrients by secreting lactate, cytokines, and androgen (6,12). Sertoli cells promote the development from germ cells to sperm via intercellular connections and regulation of the seminiferous tubule environment (9).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some studies have reported that calbindin and vitamin D receptor expression is positively correlated with testicular maturation (Kägi et al, 1988; Walterst, 2016). Moreover, it has been claimed that calbindin‐D28k protects against necrotic and apoptotic cell death by suppressing caspase‐3 and buffering calcium (Shum et al, 2022). In androgen‐deficient male mice, it was determined that TRPV5 and calbindin‐D28K mRNA and protein decreased and it returned to normal levels with testosterone administration (Hsu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…As in other systems, Ca 2+ homeostasis in the epididymis is modulated by a network of signalling pathways and cell-cell interactions. The dysregulation of Ca 2+ -regulated proteins and Ca 2+ levels in the epididymis interrupts this network and causes male infertility (Shum et al, 2022). In roosters, calbindin-D28k expression was observed in the cytoplasm of the epithelial cells lining the efferent ductules, rete testis, and epididymal duct.…”
Section: Drebrinmentioning
confidence: 99%
“…The epididymis is a post-testicular male reproductive organ to provide a region-specific and optimal luminal microenvironment for sperm maturation and storage before sperm transport to the vas deferens for ejaculation (1)(2)(3). Such epididymal microenvironment is maintained by the epithelium lining the long and highly convoluted epididymal duct, which consists of several epithelial subtypes, including basal, clear and principal epithelial cells (4)(5)(6)(7)(8). Although sperm acquire a degree of motility during epididymal transit, they remain quiescent in the epididymis, which is believed to be achieved by the slightly acidic (pH 5.5-6.8) (5,9) luminal environment built by epididymal epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…This is also evident by that impaired luminal acidification or increased bicarbonate is known to contribute to male infertility (1,7,8,15,16). In addition, the viability of the numerous sperm cells in the lumen is also supported by the reciprocal exchanges of nutrients and metabolic materials, such as membrane-containing debris, lipids and proteins (1,(4)(5)(6)(7)(8)17). Moreover, lipid homeostasis is particularly essential for sperm maturation and defects of lipid metabolism are associated with sperm impairment, male infertility, and metabolic syndromes (17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%